(untitled) (Praxis Educativa, 2025)
The objective of the writing is to carry out an analysis of the functioning of the University based on its attention to the functions of the Extension. What we are interested in proposing is an alternative to the development of the activities of the institution so that a combination with the Philosophy of Liberation can be carried out as an exercise, while the creation of links with the community occurs by valuing all the voices that participate. To do this, we propose a decolonization of the university to be able to build an institution that works and is linked as a dialogue of knowledge. This writing is the result of the reflections that emerged after the completion of the Postgraduate and Extension Diploma called “Philosophy and History of Liberation. Models of liberationist knowledge”, since there it could be clearly seen that a different future of the university is possible.